A Wireless Wearable Doppler Ultrasound Detects Changing Stroke Volume: Proof-of-Principle Comparison with Trans-Esophageal Echocardiography during Coronary Bypass Surgery - Jon-Émile Stuart Kenny; Geoffrey Clarke; Matt Myers; Mai Elfarnawany; Andrew M. Eibl; Joseph K. Eibl; Bhanu Nalla; Rony Atoui (Bioengineering, 2021)
Background: A novel, wireless, ultrasound biosensor that adheres to the neck and measures real-time Doppler of the carotid artery may be a useful functional hemodynamic monitor. A unique experimental set-up during elective coronary artery bypass surgery is described as a means to compare the wearable Doppler to trans-esophageal echocardiography (TEE). Methods: A total of two representative patients were studied at baseline and during Trendelenburg position. Carotid Doppler spectra from the wearable ultrasound and TEE were synchronously captured. Areas under the receiver operator curve (AUROC) were performed to assess the accuracy of changing common carotid artery velocity time integral (ccVTI∆) at detecting a clinically significant change in stroke volume (SV∆). Results: Synchronously measuring and comparing Doppler spectra from the wearable ultrasound and TEE is feasible during Trendelenburg positioning. In two representative cardiac surgical patients, the ccVTI∆ accurately detected a clinically significant SV∆ with AUROCs of 0.89, 0.91, and 0.95 when single-beat, 3-consecutive beat and 10-consecutive beat averages were assessed, respectively. Conclusion: In this proof-of-principle research communication, a wearable Doppler ultrasound system is successfully compared to TEE. Preliminary data suggests that the diagnostic accuracy of carotid Doppler ultrasonography at detecting clinically significant SV∆ is enhanced by averaging more cardiac cycles.